Curando a algunos doctores. La poetica medicinal de Jose Maria Arguedas - Favaron, Pedro (2023)
The present academic paper makes a medicinal interpretation, from a holistic, philosophical and indigenous understanding of health, of José María Arguedas’ famous poem “Llamado a algunos doctores” [Call to some doctors]. After reviewing some aspects of Arguedas’ literary and poetic proposal, the article will reflect on the political context and the philosophical mood (deeply Eurocentric) of the Andean literate elite that motivated the writing of this poem. Arguedas, from an empathetic identification with the indigenous sages, and in dialogue with the territories of the Peruvian highlands, invites the academic field to learn from this medicinal knowledge that has the power to reconnect intellectuals with their own heart and to reverse the modern distance that separates human beings from the territories. As will be seen towards the end of the paper, despite all the enlightened voices that predicted the disappearance of the native nations of the American continent, Arguedas’ proposal is still valid and points to the undeniable contribution that indigenous thought can make in the face of the civilization crisis of modernity.